Semi-active control of isolated and damaged structures using online damage detection. (28th August 2015) - Amini, Fereidoun; Mohajeri, Seyed Ahmad; Javanbakht, Majd
Abstract: The idea of using semi-active or active control devices within a base isolation system has been developed recently, since applying this system to building structures has some shortcomings such as the creation of large displacements at the base level and the systemʼs lack of adaptability to different seismic excitations. In this study, an integrated structural health monitoring and semi-active control scheme is proposed to enhance the seismic behavior of damaged isolated structures. The nonlinear behavior of an isolated structure is limited to the isolator level and the superstructure is assumed to remain linear. Then, using an online damage detection algorithm based on identified system Markov parameters and a semi-active fuzzy controller, the damage in the base isolator is mitigated and the seismic response of the structure is reduced. In addition, a magnetorheological damper is utilized as a well-studied semi-active actuator in the control system. The effectiveness of the proposed control system is evaluated through the numerical study of a six-degrees-of-freedom model of base-isolated buildings excited by various near-fault and far-field earthquake records. The results of the simulation show that the integrated algorithm is substantially effective in improving the dynamic behavior of isolated structures and reducing the damage in the isolator.